Climate resilient organic farming for groundnut (Arachis hypogaea)-chickpea (Cicer arietinum) cropping sequence - Mathukia, R.K.; Shekh, M.A.; Sagarka, B.K.; Vasava, M.S. (Annals of Agricultural Research, 2019)
A field experiment was conducted at Junagadh on clayey soil during 2015 to 2017 at Junagadh (Gujarat) to evaluate the potentiality of organic farming in groundnut-chickpea crop sequence in terms of productivity, profitability and soil health. Treatments comprised FYM, castor cake and vermicompost in various proportions (applied on equivalent N basis) and chemical fertilizers. Results revealed that application of FYM 1250 kg/ha + castor cake 139 kg/ha to groundnut improved growth, yield and quality parameters viz., plant height, pods/plant, test weight and oil content, and ultimately recorded significantly higher pod yield (1513 kg/ha) and haulm yield (3200 kg/ha) of groundnut as compared to RDF + FYM 5 t/ha. While manuring of vermicompost 667 kg/ha + castor cake 222 kg/ha to chickpea enhanced growth, yield and quality attributes viz., plant height, pods/plant, test weight and protein content, and eventually produced significantly higher seed yield (2269 kg/ha) and stalk yield (3272 kg/ha) of chickpea. Maximum net returns were obtained with application of FYM 1250 kg/ha + castor cake 139 kg/hain groundnut and with application of vermicompost 667 kg/ha + castor cake 222 kg/ha in chickpea. Application of FYM +castor cake to groundnut, while that of vermicompost + castor cake to chickpea significantly increased uptake of N, P and K. Application of FYM, vermicompost and castor cakeimproved post-harvest organic carbon, and availability of N, P and K in soil.